2015
DOI: 10.1016/j.jval.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations in the Diagnosis and Management of Traumatic Brain Injury: A Systematic Review and Analysis of Quality

Abstract: Threshold-guided CT scanning, adherence to Brain Trauma Foundation guidelines, and care for patients with TBI, including those with nonsurgical lesions, in specialized settings appear to be economically attractive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…262 However, a recent systematic review showed that evidence of economic benefit was available for only a minority of interventions for TBI, and much of the existing evidence was of poor quality. 279 Panel 8 summarizes interventions for which cost-effectiveness data are available.…”
Section: Cost-effectiveness Of Systems-level Management Strategiesmentioning
confidence: 99%
“…262 However, a recent systematic review showed that evidence of economic benefit was available for only a minority of interventions for TBI, and much of the existing evidence was of poor quality. 279 Panel 8 summarizes interventions for which cost-effectiveness data are available.…”
Section: Cost-effectiveness Of Systems-level Management Strategiesmentioning
confidence: 99%
“…There is an increasing pressure from governments, insurance companies, and healthcare providers to control healthcare costs [ 30 ]. The demand for high-quality evidence regarding the cost-effectiveness of treatments is also seen in TBI, where it lacks and where expensive life-saving surgical treatments can also result in a poor HRQoL [ 2 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Keywords Traumatic brain injury Á Ventilator-associated pneumonia Á Risk factors Á Incidence Á Cerebral oxygenation Á PbtO 2 Á Outcome Background Traumatic brain injury (TBI) is a leading cause of premature death and disability, with an annual incidence estimated at 500/100,000 in the USA and Europe [1][2][3]. TBIs are considered severe when, after initial resuscitation, they score B8 on the Glasgow Coma Scale (GCS) [4].…”
mentioning
confidence: 99%